Non-caseating granulomas in patients after the diagnosis of cancer: clinical characteristics and outcome - Butt, S.; Alzebdeh, R.; Kable, et al., T.D. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Background: The association between cancer and non-caseating granulomas is controversial. The aim of this study is to describe the clinical characteristics and outcome of a cohort of patients found to have noncaseating granulomas following the diagnosis of cancer.Methods: Retrospective review of medical records. Results: There were 30 patients with non-caseating granulomas following the diagnosis of cancer. There were 21 females and 14 patients were African Americans. Breast, lung, and head and neck cancers were the most common malignancies. The time between the diagnosis of cancer and non-caseating granulomas was a mean of 27.6 months (range 3 to 245 months). New mediastinal lymphadenopathy were present in 29 patients and pulmonary infiltrates or nodules were detected in 15 patients. All patients who underwent FDG-PET scan (n=18) had FDG avid findings with a mean SUV of 6.8 (range 2.8-19.4). Non-caseating granulomas were diagnosed by mediastinoscopy (12 patients), EBUS-FNA (6 patients), surgical thoracic biopsy (3 patients), transbronchial biopsy (2 patients), and other biopsies (7 patients). Patients were followed for a mean of 32.7 months (range 6-98 months) and 3 patients developed recurrence of the primary cancer. Conclusion: Non-caseating granulomas should be considered in patients with cancer who develop lymphadenopathy or pulmonary nodules. Recurrence of cancer should not always be assumed, and tissue diagnosis is essential.